The twentieth century a theological overview - Baum, Gregory (ed.) (New York Orbis Books, 1999)
The impact of historical events on theology. The great war and the theologians. The condemnation of modernism and the survival of catholic theology. After the Bolshevik revolution. Returning from exile. Catholic theology in the 1930. The great depression. The response of North American theologians. Theologians in nazi germany. The holocaust. Theological and ethical reflections. The golden years of welfare capitalism. The twilight of the giants. Emergence of a world church and the irruption of the poor. Genesis of a New World. Theological evaluation of events and movements. The myth of the twentieth century. The conciliar ecumenical movement. the impact of Vatican II. The impact of Marxis ideas on christian theology. The women's movement and theology in the twentieth century. Voices from the margins in the United States. The ecological crisis. The postmodern debate.
oldInvent-18250
Keywords: Teología; historia; Siglo Xx